MODERN APPROACHES TO TEACHING A FOREIGN LANGUAGE - Ibragimova Dilbar Sadullaevna (Research Focus International Scientific Journal, 2025)
Methods of teaching English include various approaches, strategies and techniques aimed at developing speaking, listening, reading and writing skills. Depending on the learning objectives, the age of the students and their level of language proficiency, different methods are used.